Artificial Neural Networks Algorithm for Bioconvection FloConsidering Magnetic Potential - Gurbuz-Caldag, Merve; Pekmen, Bengisen; Oztop, Hakan F. (Science and Technology Publications, Lda, 2026)
The present study develops an artificial neural network (ANN) model to predict bioconvective flow generated by magnetotactic bacteria in a square cavity with a rounded upper corner under an external magnetic field. The induced magnetic field is directly incorporated into the governing equations of bioconvection. A dataset is constructed using radial basis function (RBF) method by varying key physical parameters, including the Rayleigh, bioconvective Rayleigh, Peclet, Lewis, Hartmann and magnetic Reynolds numbers, and radius of the rounded corner. The ANN is trained and tested using multiple architectures, activation functions, and partition ratios to evaluate performance. Results indicate that a trilayer ANN with ReLU activation and an 80:20 training-to-testing split achieves the lowest mean squared error across all target outputs. Unlike conventional numerical solvers, the proposed ANN acts as a fast model capable of accurately predicting heat, mass, and bioconvective transport indicators across a high-dimensional parameter space. © 2026 by SCITEPRESS-Science and Technology Publications, Lda.
18th International Conference on Agents and Artificial Intelligence, ICAART 2026 -- 5 March 2026 through 8 March 2026 -- Marbella -- 349319
Keywords: Bioconvection; Magnetic Potential; Magnetotactic Bacteria; Neural Networks; Rounded Cavity